ANALISIS RISIKO PRODUKSI USAHATANI JAGUNG MANIS (Zea Mays Saccharata L.) DI KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Imelda Bou; Damianus Adar; Charles Kapioru (Undana Press, 2021)
Corn is a strategic food commodity in Indonesia. The purpose of this study was to determine the level of risk of sweet corn farming production and to determine the factors that influence production and the factors of risk to sweet corn farming production. The method used in this study was a survey method. The method was determined randomly. The data were obtained through intervi ews with 43 maize farmers randomly. The analysis method used was the coefficient of variation analysis and multiple linear analysis. The results showed the risk of maize farming production with moderate maize production factors was land area, fertilizer, labor, experience and pesticide with a risk level of 1% <CV 2%. The coefficient of variation in land area (0.1%), fertilizer (0.1), labor (0.1), experience (0.1) and pesticide (0.1) when compared with other production risk factors. Is the real land area and seed at alpha 5%. The source of the production risk at influence by pesticide where the pesticide variable with a coefficient value of 0.437 and a probability value of 0.001. So that the increase in the amount of pesticides has a significant effect on the risk of corn farming production.